Effect of Paricalcitol on Left Ventricular Mass and Function in CKD—The OPERA Trial - Wang, Angela Yee-Moon; Fang, Fang; Chan, John; Wen, Yue-Yi; Qing, Shang; Chan, Iris Hiu-Shuen; Lo, Gladys; Lai, Kar-Neng; Lo, Wai-Kei; Lam, Christopher Wai-Kei; Yu, Cheuk-Man (Journal of the American Society of Nephrology, 2014)
Vitamin D seems to protect against cardiovascular disease, but the reported effects of vitamin D on patient outcomes in CKD are controversial. We conducted a prospective, double blind, randomized, placebo-controlled trial to determine whether oral activated vitamin D reduces left ventricular (LV) mass in patients with stages 3-5 CKD with LV hypertrophy. Subjects with echocardiographic criteria of LV hypertrophy were randomly assigned to receive either oral paricalcitol (1 μg) one time daily (n=30) or matching placebo (n=30) for 52 weeks. The primary end point was change in LV mass index over 52 weeks, which was measured by cardiac magnetic resonance imaging. Secondary end points included changes in LV volume, echocardiographic measures of systolic and diastolic function, biochemical parameters of mineral bone disease, and measures of renal function. Change in LV mass index did not differ significantly between groups (median [interquartile range], -2.59 [-6.13 to 0.32] g/m(2) with paricalcitol versus -4.85 [-9.89 to 1.10] g/m(2) with placebo). Changes in LV volume, ejection fraction, tissue Doppler-derived measures of early diastolic and systolic mitral annular velocities, and ratio of early mitral inflow velocity to early diastolic mitral annular velocity did not differ between the groups. However, paricalcitol treatment significantly reduced intact parathyroid hormone (P<0.001) and alkaline phosphatase (P=0.001) levels as well as the number of cardiovascular-related hospitalizations compared with placebo. In conclusion, 52 weeks of treatment with oral paricalcitol (1 μg one time daily) significantly improved secondary hyperparathyroidism but did not alter measures of LV structure and function in patients with severe CKD.